Assessment of the Safety of the New Hybrid Pencil Type Energy (NP) Device Used Close to the Recurrent Laryngeal Nerve in a Porcine Model: Comparison With a Conventional Electrosurgical Knife. (April 2019) - Takeuchi, Masashi; Kawakubo, Hirofumi; Abe, Yuta; Kanazawa, Akishige; Ehara, Kazuhisa; Kinugasa, Yusuke; Kinoshita, Takahiro; Nomura, Akinari; Kitagawa, Yuko
Background . Recurrent laryngeal nerve (RLN) paralysis is mainly associated with esophagectomy, and it may result in not only other morbidities, such as aspiration pneumonia, but also in long-term issues. Therefore, an approach to prevent RLN paralysis is necessary. The present study was designed to determine the technical usability of the new hybrid pencil type energy (NP) device developed by Olympus Corporation (Tokyo, Japan) and compare it with a conventional electrosurgical knife (EK) for resection around the RLN lymph nodes. Methods . This nonsurvival (acute) study included 10 pigs (20 RLNs) and investigated the threshold for thermal RLN damage with the NP device and a conventional EK. To obtain basic information for our study, a preliminary experiment for heat spread was performed. Results . When using the EK device, the amplitude value disappeared at a distance of 1 mm from the RLN, but when using the NP device, the amplitude value was maintained up to a distance of 0.5 mm. There were significant differences at distances of 0 mm, 0.5 mm, and 1 mm between the NP and EK devices. Furthermore, heat spread was lower with the NP device than with the EK device. Conclusions . The new energy device developed by Olympus Corporation was found to be technically safe for resection of the RLN lymph nodes in a porcine model. To the best of our knowledge, this is the first study to demonstrate the potential advantages of using this new energy device in a clinical aspect.